MILITARY AND HISTORICAL DISCIPLINE IN THE HIGHER MILITARY EDUCATIONAL ESTABLISHMENTS OF UKRAINE: PROBLEMS AND PROSPECTS FOR CHANGES - Ovcharenko, V. V.; Semenov, S. S.; Falko, S. А. (Honor and Law, 2019)
The problems of teaching military and historical subjects in higher military educational institutions of Ukraine are considered.The proposals to improve the promising project of teaching the subject “Histories of wars and military art” are put forward in the Academy of National Guard of Ukraine. The influence of this direction of military science on the formation of professional qualities of future officers is considered.The necessity of spreading research of military history is proved. The purpose of the proposed work is the use of modern scientific experience in the learning process and during the organization of cadets` combat training.